On Dinosaur Reconstruction: An Introduction to Important Topics of Paleontology and Dinosaurs - Florides, Georgios A.; Christodoulides, Paul (My University, 2021)
Many people may be interested in Paleontology since the subject allows for large amounts of imagination and freedom in the creation of scenes. Dinosaurs draw the biggest interest because of their diversity in peculiar forms and often unusually large size of many species. There are people like artists who help the field paleontologists to describe, interpret and reconstruct fossils, and others that create drawings, restorations, sculptures and, most recently, computer animations for science, art and joy. To this end, a successful professional should have specific knowledge that will allow them to produce high-quality work. The current paper aims at: 1) providing knowledge on various topics of Paleontology, in order to understand the time scale of life on earth, its evolution and diversity; 2) generating appreciation for the evolution of climatic conditions, continental plates and movement and the Mesozoic environment in which dinosaurs evolved; 3) offering an understanding of scientific nomenclature used in Paleontology, and interpretation of drawings and meanings; 4) helping one to realize how scientists extract information from bones, tracks, eggs, embryos and other remains; 5) examining the physiology of dinosaurs, their metabolism, behaviors, growth rates estimated lifetime and diet; and 6) leading to the understanding of the relations between different dinosaur species and how Paleontologists complete missing parts from uncomplete skeletons. Examining the evolution of life, we observe that life began about 3.8 billion years ago in the deep sea. The first simple animals such as worms and jellyfish appeared in the oceans around 600 mya. The crust of the earth continuously moves to produce changes in the land masses and changes in the climatic conditions that affect the evolution of life. The life of the earth is divided into geological eras. At the end of each geological era, a major event of extinction occurred, which every time obliterated important groups of life. Dinosauria was one of the most successful clades of animals that lived on terrestrial ecosystems for over 160 million years, but was extinct at one of the major extinction events 66 mya. The remains of animals allow scientists and artists to recreate their forms usually in great detail and extract a lot of information about their lives. The paper describes in detail how and where to find information and explains how to interpret them in order to understand the meanings. The paper presents all the above in a simplified way giving the required knowledge without using difficult scientific terms and provides the essential knowledge to the interested person to appreciate the science of Paleontology.
Keywords: Skeletal Reconstruction; Dinosaur Modeling; Geological Time Chart; Extinct Animals